2022
DOI: 10.1007/s00436-022-07664-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular (cox1), geographical, and host record investigation of monogeneans Mazocraes australis (Mazocraeidae), Polylabris sillaginae, and P. australiensis (Microcotylidae)

Abstract: This study determines the occurrence and molecular characterisation of Monogenea from three commercially important Australian fish: Australian sardine Sardinops sagax (Jenyns), Australian anchovy Engraulis australis (White), and eastern school whiting Sillago flindersi McKay. Earlier studies have provided only morphological species identification, whereas this study combines both morphological and molecular methods. A total of 247 fish across 3 species, sourced from the New South Wales and Victorian coasts, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Overall, the presence of Polyopisthocotylea in distinct localities is not unusual and has been previously challenged by cox 1 barcodes. Consequently, the taxonomic and geographic status of several polyopisthocotyleans has been validated (see ( Hossen et al, 2022a , 2022b ). Hossen et al (2022b) demonstrated with cox 1 barcodes the presence of Allogastrocotyle bivaginalis both in Mediterranean waters, off Algeria (report by Bouguerche et al, 2019a , Bouguerche et al, 2019b ) and in Australian waters (Victoria) of the southwest Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the presence of Polyopisthocotylea in distinct localities is not unusual and has been previously challenged by cox 1 barcodes. Consequently, the taxonomic and geographic status of several polyopisthocotyleans has been validated (see ( Hossen et al, 2022a , 2022b ). Hossen et al (2022b) demonstrated with cox 1 barcodes the presence of Allogastrocotyle bivaginalis both in Mediterranean waters, off Algeria (report by Bouguerche et al, 2019a , Bouguerche et al, 2019b ) and in Australian waters (Victoria) of the southwest Pacific.…”
Section: Discussionmentioning
confidence: 99%